The Potential of Ethanol Extract of Temu Kunci (Boesenbergia rotunda (L.) Mansf.) Rhizomes as an Anticonvulsant Against Male White Rats - Pabenjanan, Agustin Yumita; Dwitiyanti; Risda Hidayati Winza Putri (Jurnal Jamu Indonesia, 2024)
The temu kunci extract was previously reported to have quite good antioxidant activity. One of the causes of seizures is oxidative stress. There has yet to be much exploration of temu kunci extract as an anticonvulsant. This study examines the anticonvulsant activity of 70% ethanol extract of Boesenbergia rotunda (L.) Mansf. against male white rats. The parameters observed were the onset and duration of HLE (Hind Limb Extension) with a digital electroconvulsiometer with a power of 150 mAmp and 50 hertz for 0.2 seconds. The test group was divided into five treatment groups, namely group 1 to group 3 (K1-K3), with extract doses: 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW, respectively, while K4 was a positive control using valproic acid (Depakote 1.54 mg/kgBW), and normal control group (K5) with Na-CMC 0.5%. The results were analyzed using one-way ANOVA and continued with the Tukey test. From the research carried out, information was obtained that 70% ethanol extract of temu kunci at a dose of 400 mg/kgBB had the best potential as an anticonvulsant in prolonging the onset of HLE (seconds) and shortening the duration of HLE (seconds) in mice comparable to the positive control. Temu kunci has the potential to be further developed as an anticonvulsant drug candidates in the future.